Evidence of lateral heat transfer during laser assisted atom probe tomography analysis of large band gap materials - Bachhav, Mukesh N.; Danoix, R.; Vurpillot, F.; Hannoyer, Beatrice; Ogale, Satishchandra B.; Danoix, F. (Applied Physics Letters, 2011)
Investigation of wustite (FeO), iron (Fe), and silicon (Si) specimens by infrared laser assisted three dimensional atom probe tomography shows evidence of confined surface absorption of the laser energy as the mechanism of laser assisted field evaporation for high band gap materials. The absorption region is shown to be located on the laser illumination side, close to the specimen apex. A simple model based on thermal diffusivity and spatial extent of the absorption region is derived and applied to the experimental results. The values of thermal diffusivity thus obtained are in good agreement with the published data. (C) 2011 American Institute of Physics. [doi:10.1063/1.3622647]